2011
DOI: 10.1124/jpet.111.180620
|View full text |Cite
|
Sign up to set email alerts
|

Catalase and Superoxide Dismutase Conjugated with Platelet-Endothelial Cell Adhesion Molecule Antibody Distinctly Alleviate Abnormal Endothelial Permeability Caused by Exogenous Reactive Oxygen Species and Vascular Endothelial Growth Factor

Abstract: Reactive oxygen species (ROS) superoxide anion (O 2 . ) and hydrogen peroxide (H 2 O 2 ) produced by activated leukocytes and endothelial cells in sites of inflammation or ischemia cause endothelial barrier dysfunction that may lead to tissue edema. Antioxidant enzymes (AOEs) catalase and superoxide dismutase (SOD) conjugated with antibodies to platelet-endothelial cell adhesion molecule-1 (PECAM-1) specifically bind to endothelium, quench the corresponding ROS, and alleviate vascular oxidative stress and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 39 publications
1
60
0
1
Order By: Relevance
“…As the important products of oxidative stress, ROS generation during cerebral ischemic injury was suggested to cause severe brain damage (Olmez and Ozyurt 2012). Previous studies have shown that incubation of endothelial cells with ROS promotes cellular contraction and increases the permeability of endothelial monolayers, finally causing endothelial cell death and further deterioration of BBB (Han et al 2011;Pun et al 2009). In this study, ROS levels were measured using flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As the important products of oxidative stress, ROS generation during cerebral ischemic injury was suggested to cause severe brain damage (Olmez and Ozyurt 2012). Previous studies have shown that incubation of endothelial cells with ROS promotes cellular contraction and increases the permeability of endothelial monolayers, finally causing endothelial cell death and further deterioration of BBB (Han et al 2011;Pun et al 2009). In this study, ROS levels were measured using flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The other haematological indices and iron concentration in blood plasma were also significantly lower in the experimental group compared to control. Oxidative stress has been defined as a disturbance of equilibrium between the production of reactive oxygen species and the antioxidant defence system (P i et al 2010) including superoxide dismutase (SOD), catalase, and glutathione peroxidase (GSH-Px) (Han et al 2011). Increased lipid peroxidation has been associated with iron deficiency in rats and human patients (Kumerova et al 1998), but the topic remains controversial (Acharya et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Pretpostavljeni genoprotektivni mehanizam Sal B u pretretmanu naše studije mogao bi da bude povećanje intracelularnog antioksidativnog enzimskog kapaciteta (38). Upotreba kineske žalfije (Salvia miltiorrhiza), koja kao jedan od sastojaka ima Sal B, može da poveća aktivnost katalaze i glutation peroksidaze (39), dva enzima koja su odgovorna za konverziju vodonik-peroksida do vode i kiseonika (40).…”
Section: Diskusijaunclassified